Konsep, Jenis dan Solusi Zakat di Indonesia - Hidayat, Amirul; Bahri, Saiful (STISIP Widyapuri Mandiri Sukabumi, 2024)
At the time of nisab, every Muslim is required to pay zakat, which is one of their religious duties. It may be seen as a transgression of Islamic principles to fail to pay zakat. Islam, property ownership, nisab and haul fulfillment, and zakat payment capability are the pillars and criteria of zakat. According to the Quran, there are eight distinct classes that are eligible to receive zakat. The author used a literature review approach to gather references on zakat, its concepts, its distribution, its types, and difficulties in Indonesia, as well as potential remedies to those concerns. More extensive zakat education and outreach, improved zakat institution transparency and accountability, tech-enabled zakat process, party collaboration, and new, sustainable zakat programmes to address social issues are all part of Indonesia's zakat selection